Explaining the Poor Performance of Consumption‐based Asset Pricing Models - Campbell, John Y.; Cochrane, John H. (Journal of Finance, 2000)
We show that the external habit‐formation model economy of Campbell and Cochrane (1999) can explain why the Capital Asset Pricing Model (CAPM) and its extensions are betterapproximate asset pricing models than is the standard onsumption‐based model. The model economy produces time‐varying expected eturns, tracked by the dividend–price ratio. Portfolio‐based models capture some of this variation in state variables, which a state‐independent function of consumption cannot capture. Therefore, though the consumption‐based model and CAPM are both perfect conditional asset pricing models, the portfolio‐based models are better approximate unconditional asset pricing models.